Neurogenesis-independent antidepressant-like effects of enriched environment is dependent on adiponectin. (July 2015) - Nicolas, Sarah; Veyssière, Julie; Gandin, Carine; Zsürger, Nicole; Pietri, Mariel; Heurteaux, Catherine; Glaichenhaus, Nicolas; Petit-Paitel, Agnès; Chabry, Joëlle
Abstract : Highlights: Environmental enrichment (EE) reduces anxiety and depression-like behaviors in a mouse model of depression. EE strongly increases hippocampal neurogenesis. Adiponectin, an adipose-derived hormone, is a main contributor of EE-induced behavioral benefits. Adiponectin actions do not involved hippocampal neurogenesis since no difference was observed in brains from wt and adiponectin-null mice. EE does not modify the plasma level of adiponectin but favors its passage from the blood to the cerebrospinal fluid. Summary: Environmental enrichment (EE) that combines voluntary physical exercise, sensory and social stimuli, causes profound changes in rodent brain at molecular, anatomical and behavioral levels. Here, we show that EE efficiently reduces anxiety and depression-like behaviors in a mouse model of depression induced by long-term administration of corticosterone. Mechanisms underlying EE-related beneficial effects remain largely unexplored; however, our results point toward adiponectin, an adipocyte-secreted protein, as a main contributor. Indeed, adiponectin-deficient (adipo −/− ) mice did not benefit from all the EE-induced anxiolytic and antidepressant-like effects as evidenced by their differential responses in a series of behavioral tests. Conversely, a single intravenous injection of exogenous adiponectin restored the sensitivity of adipo −/− mice to EE-induced behavioral benefits. Interestingly, adiponectin depletion did not prevent the hippocampal neurogenesis induced by EE. Therefore, antidepressant properties of adiponectin are likely to be related to changes in signaling in the hypothalamus rather than through hippocampal-neurogenesis mechanisms. Additionally, EE did not modify the plasma levels of adiponectin but may favor the passage of adiponectin from the blood to the cerebrospinal fluid. Our findings provide advances in the understanding of the anxiolytic and antidepressant-like effects of EE and highlight adiponectin as a pivotal mediator.